Combined traditional and natural therapies in patients with alopecia areata - Natacha López Pupo; María Elena Tablada Robinet; Caridad Jacas García; Ana Lucía Jacas Portuondo; Marhyan Solano Pérez (Centro Provincial de Información de Ciencias Médicas, 2018)
A study of therapeutic intervention in 30 patients with diagnosis of patchy alopecia areata, assisted in the Dermatology service of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba  was carried out from June, 2014 to the same month in 2015, aimed at determining the effectiveness of the combined Chinese traditional therapy and the natural one (Bach flowers remedies for transpersonal pattern, acupuncture with hammer of 7 tips and local massage with ginger rhizome), for which  a study group was formed which received it and another control  group which was treated with steroid cream (triamcinolone 0,1%). Patients from the age group 25 - 34 years and male sex, were evaluated at the beginning, and then at fourth, eighth and twelfth weeks.  The combined traditional and natural therapies in patients with alopecia areata provided a better response and there were no secondary effects, what demonstrated its effectiveness on this respect.